2020
DOI: 10.3390/su12093556
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and Foreign Direct Investment—The Moderating Role of Quality Institutions

Abstract: Considering the importance of foreign direct investment (FDI) inflows for the sustainable economic advancement of a host country, this paper investigates the financial development and FDI nexus, using institutional quality as a moderator. The sample consists of 79 Belt and Road Initiative (BRI) partner countries, as these countries are entering a new age of integration, foreign trade, and mutual development. The empirical findings of conventional and robust estimators show that the financial development of BRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 87 publications
(139 reference statements)
1
52
0
4
Order By: Relevance
“…This very matter has also been carefully handled to observe the actual fluctuation in the wealth efficiency. Another study suggested that findings should be robust on the main variables and alternative methodologies to alternative proxies [51]. It has been ensured through using multiple regression models in the study.…”
Section: Generalized Methods Of Moments Analysis For Both Covariance-mentioning
confidence: 99%
“…This very matter has also been carefully handled to observe the actual fluctuation in the wealth efficiency. Another study suggested that findings should be robust on the main variables and alternative methodologies to alternative proxies [51]. It has been ensured through using multiple regression models in the study.…”
Section: Generalized Methods Of Moments Analysis For Both Covariance-mentioning
confidence: 99%
“…Empirically, different studies have shown the link between financial developments (FD) and trade openness with FDIs. As a demonstration of this, Islam et al (2020); Desbordes and Wei (2017); Havi and Enu (2014) found a positive significant impact of financial development on FDI. On the other hand, Dellis (2018) and Tsaurai and Makina (2018) publicized the inconclusive results about the influence of financial development on FDI.…”
Section: Introductionmentioning
confidence: 90%
“…Foreign direct investment has a significant influence on China's regional economic growth [47]. The research has also shown a significant relationship between FDI and economic growth [48].…”
Section: Foreign Direct Investmentmentioning
confidence: 97%